Density-dependent prophylactic immunity in social insects: behavioural and physiological components - Simões, Talitta Guimarães (2014)
The Density-Dependent Prophylaxis (DDP) hypothesis predicts that organisms can invest more in immunological defence when in high densities. In insects, this hypothesis has been confirmed for many groups. However, most of these studies did not show an overall increase in analysed defence mechanisms and they did not analysed behavioural defences. On the first chapter, we discuss how DDP could have emerged and fixed in different groups, in accord with the degree of sociality. We then propose the hypothesis that there should be changes on DDP investment along a continuum that ranges from strictly solitary insects to eusocial insects. Thus, strictly solitary insects did not develop any plastic response of immune system (neither physiological nor behavioural) to an artificial density increase; insects that eventually undergo natural density variations can show plastic response of immune system, however, manifested only in physiological responses to protect themselves; insects that necessarily experiment natural changes in density (i.e. gregarious insects) must show plastic responses, manifested in physiological defence, but occasionally in behavioural also; and insects with high density as a predominant character along its life (i.e. eusocial insects) must show plastic response, manifested in behavioural responses, to protect the colony as a hole. Chapter 2 tests this hypothesis in an eusocial bee, Melipona quadrifasciata, analysing if DDP response to artificial density manipulation and if that is expressed on investment in physiological or behavioural defence. For this, workers recently emerged were kept alone, with one other nestmate or in high density for 10 days. Per capita interactions were analysed to estimate the connectivity between individuals, showing that connectivity was related to density. Two parameters in physiological immune system were tested, encapsulation response and haemocyte density in haemolymph, not finding differences between individuals kept in different density/connectivity treatments for any of these parameters. To analyse DDP investment related to behavioural defence we exposed the bees kept in different densities to another nestmate contaminated with Beauveria bassiana spores. Bees kept in high density/connectivity were extremely aggressive with the contaminated bee, many times killing it. This proved to be an important defence mechanism at colony level. On the other hand, bees kept alone or with only another nestmate did not show effective behavioural defence. We conclude that Melipona quadrifasciata shows DDP, investing in behavioural defence, in accord with our hypothesis exposed on the first chapter.